1988
DOI: 10.1063/1.866693
|View full text |Cite
|
Sign up to set email alerts
|

Streaming tearing instability in the current sheet with a super-Alfvénic flow

Abstract: The tearing instability in a current sheet, which has a sub-Alfvénic or super-Alfvénic plasma flow in the current layer, is investigated based on the linearized compressible magnetohydrodynamic (MHD) equations. An initial-value method is employed to obtain the linear growth rate and eigenmode profiles of the fastest growing mode. The results show that for a sub-Alfvénic plasma flow parallel to the neutral sheet, the growth rate of the tearing instability is only slightly larger than that of the pure tearing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
22
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 14 publications
8
22
0
Order By: Relevance
“…It is noted in the solar wind, av can be larger than as. In our previous calculations Wang, Lee, and Wei, 1988), only cases with av = aB and q~o = 0 are considered. The pressure balance condition has been used to obtain the density profile in Equation (7).…”
Section: Streaming Sausage Kink and Tearing Instabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted in the solar wind, av can be larger than as. In our previous calculations Wang, Lee, and Wei, 1988), only cases with av = aB and q~o = 0 are considered. The pressure balance condition has been used to obtain the density profile in Equation (7).…”
Section: Streaming Sausage Kink and Tearing Instabilitiesmentioning
confidence: 99%
“…Recently, Lee et aL (1988) and Wang, Lee, and Wei (1988) found that the streaming sausage, kink, and tearing instabilities can be excited in a current sheet with a super-Alfv6nic plasma flow. The streaming sausage and kink instabilities, similar to the Kelvin-Helmholtz instability, are caused by the sheared plasma flow.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the initial tearing mode based on the relativistic Harris equilibrium is still constrained by k x λ < 1 (i.e., from relativistic energy principle) [40], as in the non-relativistic limit. A temperature anisotropy [41,42] or the velocity shear associated with the outflow jet [43][44][45] may change the stability criterion, however, to resolve this issue in the relativistic regime is beyond the scope of this Letter. Fig.…”
mentioning
confidence: 99%
“…The elongation brings a slowlymoving, confined plasma into the solar wind flowing along the streamer stalk and introduces velocity shear into the system. When the shear is large enough, a streaming sausage mode instability Wang et al, 1988) may develop to trigger the reconnection, producing the disconnected plasma blobs. Besides the sausage mode instability, there are also two other possible processes contributing to the occurrence of reconnection.…”
Section: Introductionmentioning
confidence: 99%